2017
DOI: 10.1039/c6ra27686e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of hydrogen production of a Cu–TiO2nanocomposite photocatalyst combined with broad spectrum absorption sensitizer Erythrosin B

Abstract: A broad spectrum absorption photocatalytic system has been expected for a long time, especially for catalysts where the absorption mainly concentrates on the ultraviolet region, like TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…Visible light absorption efficiency is increased incorporation of metallic Cu nanoparticles in the NÀ TiO 2 system (CuÀ NÀ TiO 2 ), which can be ascribed to the Surface Plasmon Resonance peak of plasmonic Cu NPs. [20] Pl spectra evidenced a reasonable reduction of peak intensity for CuÀ NÀ TiO 2 to that of NÀ TiO 2 ( Figure 1f). This is due to the migration of photo-generated electrons in CB of NÀ TiO 2 to Cu and restricts recombination.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Visible light absorption efficiency is increased incorporation of metallic Cu nanoparticles in the NÀ TiO 2 system (CuÀ NÀ TiO 2 ), which can be ascribed to the Surface Plasmon Resonance peak of plasmonic Cu NPs. [20] Pl spectra evidenced a reasonable reduction of peak intensity for CuÀ NÀ TiO 2 to that of NÀ TiO 2 ( Figure 1f). This is due to the migration of photo-generated electrons in CB of NÀ TiO 2 to Cu and restricts recombination.…”
Section: Resultsmentioning
confidence: 79%
“…In the UV‐Vis diffuse reflectance spectra (DRS) of Cu−N−TiO 2 , a reasonable improvement in the absorption of light in the visible region to that of bare N−TiO 2 (Figure 1e). Visible light absorption efficiency is increased incorporation of metallic Cu nanoparticles in the N−TiO 2 system (Cu−N−TiO 2 ), which can be ascribed to the Surface Plasmon Resonance peak of plasmonic Cu NPs [20] . Pl spectra evidenced a reasonable reduction of peak intensity for Cu−N−TiO 2 to that of N−TiO 2 (Figure 1f).…”
Section: Resultsmentioning
confidence: 95%
“…The synthesis of a co-catalyst, supported or decorated with metallic nanoparticles, has been processed in more than one step [22,23,24,25,26,27,28] employing high temperature or several solvents, surfactants, and precursors, some of which are toxic or highly harmful to the environment [23,24]. Previous works have reported that TiO 2 was decorated by photodeposition [29], electrodeposition [28], microemulsion [24], chemical [30], and radiolytic reduction [31]. The one-pot synthesis offers a green chemistry and sustainable alternative necessary today.…”
Section: Introductionmentioning
confidence: 99%
“…Another important class of sensitizers employed for photocatalytic hydrogen production are metal free organic dyes; although initial reports concerned the use of fluorescent dyes such as Eosin Y, Rhodamines, [71,72] Rose Bengal [73] and Erythrosin B, [74] more recently research focused on those having a donor-acceptor D-π-A architecture, that was found to be highly versatile and particularly suitable when an efficient charge separation was required. In details, these kinds of sensitizers are characterized by the presence of three submolecular units: an electrondonating group (D), a π-spacer (π), and an electron-accepting group (A).…”
Section: Metal-free Organic Dyesmentioning
confidence: 99%